Performance of bubble deck slab - Liew, Mun Kai (2018)
Slab structure is considered as one of the largest structural members that consumes large amount of concrete in a building construction. Concrete is the single most widely used material in the world. Unfortunately, concrete has a problem [6]. Concrete created substances that polluted the environment. In the 1990’s, Jorgen Bruenig had invented the first biaxial voided slab called bubble deck slab. Bubble deck slab system acts as a method of practically removing the concrete volume from the middle of a floor slab for not performing any structural purpose [1]. Thereby it reduces the structural dead weight dramatically as significant amount of concrete volume has been ‘evacuated’. The voids in the middle of a flat slab are filled with plastic spheres that remove the self-weight of slab. Impressively, the removal of self-weight of the slab approximately result by 35% in removing the restriction of high dead loads and short spans [9]. The reduced amount of concrete volume has led to the decreasing production of carbon dioxide indirectly and by using recycled plastic as an alternative replacement material for concrete, bubble deck slab system can be considered as a slab construction method that contributes to green technology. The performance of bubble deck slab was determined with comparisons being made against the conventional solid slab which was based on the flexural strength, type of failures and the crack pattern and propagation. The specimens used were 1500mm by 1500mm for width and length with a thickness of 285mm. A total of 25 HDPE hollow plastic bubble balls of thickness 230mm were used for the bubble deck slab specimen. The reinforcement steel bar meshes used were 6mm thick of mild yield steel. Furthermore, a total of 12 concrete cubes of dimensions 150 cubic mm with concrete grade 30 were divided into 4 kinds of concrete curing periods with 3 each which were 3 days, 7 days, 14 days and 28 days before compression test was conducted. Apart from that, tensile test was carried out for high yield steel size 8mm and 10mm while mild steel are 6mm, 8mm and 10mm. Flexural test was done on both the bubble deck slab and conventional solid slab by the application of three point flexural testing after both slabs were cured by water for a total of 28 days. From the results obtained, the percentage drop of shear strength was 53% for bubble deck slab whilst 36% for conventional solid slab with comparison with design shear strength of 136.64 kN. The modulus of rupture of bubble deck slab was 447.51 MPa which was lower than conventional slab, 608.09 MPa. It can be concluded that bubble deck slab with lower self-weight and same dimensions as compared to conventional solid slab has a higher ultimate load than conventional solid slab. Moreover, at peak load, microcracking occurred at the sides near the middle of the slab.